Clinical coordination across care levels according to medical specialty in the Catalan health system. (30th September 2020) - Campaz, D; Esteve-Matalí, L; Vargas, I; Sitjas, E; Plaja, P; Sanchez, E; Ramon, I; Medarde, E; Vázquez, M L
Abstract: Background: In primary care-based national health systems, cross-level clinical coordination is a priority, as it contributes to quality of care and efficiency. Studies show that clinical coordination may vary depending on doctoŕs specialty. The study's aim was to determine the differences in experience and perception of clinical coordination and their related factors according to the doctor's specialty in the Catalan health system Methods: Cross-sectional study, based on an on-line survey applying the COORDENA-CAT questionnaire to 1666 secondary care doctors. Descriptive and multivariate analysis were used to compare five groups of specialties (potentially decentralised, hospital-based, internal-medicine/geriatrics, gynaecology, and paediatrics), for experience, perception and factors related to clinical coordination. Results: Clinical coordination experience was relatively high in all groups, with differences when comparing with decentralised specialties; hospital-based specialties and internal medicine/geriatrics presented lower care consistency and follow up across levels, while gynaecology and paediatrics showed higher accessibility. General perception of coordination was low, being worse in hospital-based specialties (PR:0.80, 95%CI0.72-0.89) and better in gynaecology (PR:1.36, 95%CI1.18-1.56). Moreover, hospital-based specialties reported lower use of coordination mechanisms and less interaction with doctors from the other level (PR:0.42, 95%CI0.23-0.72), than gynaecology (PR:2.04, 95%CI1.22-3.45). Conclusions: Doctors' experience and perception of clinical coordination was lower among hospital-based specialties and internal medicine/geriatrics and higher in gynaecology and paediatrics. These differences may be explained by complexity, coordination needs, level of specialty decentralisation or related factors. Further research is needed to understand such differences and consider the coordination needs of each specialty to improve cross-level clinical coordination. Key messages: Differences between specialities might be explain by the complexity, level of specialty decentralisation or factors related to clinical coordination. Clinical coordination needs of each specialty should be deeply explored to improve cross-level clinical coordination.